Oral Squamous Cell Carcinoma: an Epidemiological Study Conducted at Santa Casa de Misericórdia Hospital of Fortaleza - Ce, Brazil - Teixeira, Ana Karine Macedo (2009)
The purpose of this study was to identify the epidemiological profile of oral squamous cell carcinoma (SCC) patients, who were treated at Santa Casa de Misericórdia hospital in Fortaleza - CE, Brazil, from 1999 to 2005. This was a descriptive, cross-sectional study. The studied population comprised 225 cases of oral cancer. Data were collected from the register book of head and neck surgeries and from patient health charts of Santa Casa hospital. The following variables were evaluated: age, sex, patient origin, cancer clinical and pathologic staging, anatomical localization and treatment. Results showed that 69.2% of the cases occurred in men, within the age range of 26 to 98 years. The most common anatomical localizations were mouth floor (22.7%) and tongue (21.8%). As per cancer staging, 52.4% of patients were classified as stage III or IV, with a 40% regional metastasis. Most of the patients were submitted to surgery associated to radiotherapy (57.2%). A significant statistical relation (p<0.05) was found between the variables sex and age, sex and anatomical localization and this latter with age. The results suggest the need of implementing a prevention and oral cancer control policy in Ceará State, Brazil, aiming at the reduction of new cases, early diagnosis and better prognostic, besides the treatment of these neoplastic diseases.